Stories of the role musicking plays in coping with the COVID-19 pandemic in South Africa. (July 2022) - van der Merwe, Liesl; Erasmus, Ewie; Morelli, Janelize; Potgieter, Hetta; Modise, Julia; Viviers, Etienne; Meyer, Joy; Engelbrecht, Christelle; Jacobs, Daniel; Shongwe, Sibusiso; Lerumo, Kagiso
The purpose of this narrative study is to explain the role that musicking plays in coping with the COVID-19 pandemic for 11 South African musicians. The research question is: How do the stories of 11 South African musicians explain the role that musicking plays in coping with the COVID-19 pandemic? There have been studies on how music helps in therapeutic and everyday settings, but there has been limited research on the role musicking plays in coping with pandemics. The 11 author-participants in the study have lived through this pandemic, and their stories served as the data. We used a narrative coding scheme to enable co-coding. Our findings are a collaborative interpretation of our analyses and are represented as a fictionalized dialogue. This dialogue revealed that the COVID-19 pandemic had a range of psychological effects on the participant researchers. Musicking contributed to proactive and reactive coping strategies, including listening to music actively, making music with others virtually and in their homes, finding solidarity through engaging with musical icons, allowing them to connect with others, escape, focus, relax, and find hedonic well-being and hope. Further research will be needed to understand the roles musicking may play in coping with pandemics.